2012
DOI: 10.1080/08995605.2012.642292
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Cognitive Appraisal on Combat Exposure and Psychological Distress

Abstract: Applying Cognitive Appraisal Theory (Lazarus & Folkman, 1984), this study sought to determine the mediating effect of cognitive appraisal on combat exposure and psychological distress. A total of 3,002 military personnel completed measures of combat exposure, cognitive appraisal of combat-related events, and psychological distress either during or soon after combat operations in Afghanistan. Bootstrapping was employed to test the mediation model. Cognitive appraisal mediated the relationship between combat exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
3
9
0
3
Order By: Relevance
“…For example, consistent with literature from earlier wars, appraisals of combat have been found to be better predictors of PTSD than combat itself, and appraisals of combat can mediate the relationship between serving in combat and psychological distress (McCuaig Edge & Ivey, 2012), both during and shortly after service (Bush, Skopp, McCann, & Luxton, 2011). …”
Section: Appraisals Of Wartime Military Servicesupporting
confidence: 61%
“…For example, consistent with literature from earlier wars, appraisals of combat have been found to be better predictors of PTSD than combat itself, and appraisals of combat can mediate the relationship between serving in combat and psychological distress (McCuaig Edge & Ivey, 2012), both during and shortly after service (Bush, Skopp, McCann, & Luxton, 2011). …”
Section: Appraisals Of Wartime Military Servicesupporting
confidence: 61%
“…Thus, a partial mediation model (which assumes direct paths from stress to cognitive appraisal) and a full mediation model (which removes the direct path from stress to psychological health) were tested. Several previous studies have demonstrated the mediating role of cognitive appraisal in the relationship between different variables, such as stress and burnout (Gomes, Faria, & Gonçalves, 2013), stress and psycho-physiological reactions (Goh, Sawang, & Oei, 2010), resilience factors and psychological distress (Schaubroeck, Riolli, Peng, & Spain, 2011), and combat exposure and psychological distress (McCuaig Edge & Ivey, 2012). However, in this study, the mediating effect of cognitive appraisal was tested using a multidimensional measure of both primary and secondary cognitive appraisal, which is still not frequently used in occupational stress research (Carpenter, 2016).…”
mentioning
confidence: 91%
“…Support for Hypothesis 8, that increases in strain would also be associated with increases alcohol consumption, was also expected. Both findings align with previous research and highlight the importance of understanding the influence of Combat Exposure on deployed members' mental health (Bouchard, Baus, Bernier, & McCreary, 2010;Fear et al, 2010;Fetzner et al, 2013;Jacobson et al, 2008;McCuaig Edge & Ivey, 2012;Ramchand et al, 2011;Saxon et al, 2001;Skomorovsky & Lee, 2012;Wilk et al, 2010).…”
Section: Study 2 Discussionsupporting
confidence: 88%